Age-related transversal changes in craniofacial sutures of the anterior viscerocranium in growing rats - Gorucu-Coskuner, Hande; Al-Yassary, Mustafa; Billiaert, Kelly; Kiliaridis, Stavros; Antonarakis, Gregory S. (Frontiers in Physiology, 2023)
Objective: To evaluate the dimensional changes that occur in the internasal and nasopremaxillary sutures, and related transverse craniofacial dimensions, of rats from 4 to 38-weeks of age. Methods: Four groups of twelve male Wistar rats were sacrificed at different ages (4-weeks (immature), 16-weeks (adolescent), 26-weeks (young adult), 38-weeks (adult)). The rats were scanned with a high-resolution micro-computed tomography imaging device with 90µm voxel size and 45x45mm field of view (FOV) to obtain images of the viscreocranium, and with 10µm voxel size and 5x5mm FOV to obtain images of the internasal and left nasopremaxillary sutures. The nasal bone width, transverse width between the nasopremaxillary sutures and interzygomatic width were measured as craniofacial measurements. The endocranial, ectocranial and mean suture widths (cross-sectional area between endocranial and ectocranial borders/suture height), and suture height were measured at 5 frontal planes with 1.2mm intervals. Outcomes were compared at different ages, and correlation coefficients were used to assess the relationship between craniofacial and suture changes. Results: All transverse craniofacial dimensions increased significantly from 4-16 weeks of age (p<0.001). After 16-weeks of age, the only significant increase was observed in interzygomatic width (p=0.02), between 26-38 weeks. In both the internasal and nasopremaxillary sutures, the endocranial suture mean widths decreased from 4-16 weeks (p<0.001 and p=0.002, respectively), but did not show any significant change after 16-weeks of age. The ectocranial internasal suture width decreased from 4-16 weeks (p<0.001), increased until 26-weeks (p=0.035), and subsequently decreased (p<0.001). The nasopremaxillary suture widths decreased from 4-38 weeks to varying degrees in different frontal planes. Except for the internasal ectocranial suture width, all suture measurements were found highly and negatively correlated with the transverse craniofacial dimensions. The height of the sutures increased with time, with the most significant changes occurring between 4-16 weeks of age (p<0.001). Conclusions: Although the internasal and nasopremaxillary endocranial suture widths nearly reach their final widths during adolescence, the changes in the ectocranial and mean suture widths continue into early adulthood. These results may serve as a reference for future studies aiming to evaluate the effects of functional demands on suture development and dimensional changes of the viscerocranium.